MOBILIZATION OF VEGETABLE AND CUCURBIT CROP GENETIC RESOURCES IN THE 21st CENTURY - A. M. Artemyeva; O. A. Zvereva; T. N. Kozhanova; D. L. Kornyukhin; T. M. Piskunova; T. N. Smekalova; I. G. Chukhina; L. V. Bagmet (Труды по прикладной ботанике, генетике и селекции)
The worldwide collection of vegetable and cucurbit crops kept in VIR includes 50,019 accessions of various status -representatives of 27 families, 145 genera, 475 species received since 1923 from 95 countries of the world. Biodiversity of cultivated species and their wild relatives, especially from their centres of origin and diversity, is adequately represented in the collection. Currently, the completion of the collection is conducted in the following areas: collection of wild species and local forms with a high level of resistance to biotic and abiotic stresses, and with valuable biochemical composition; replenishment of the collection with accessions missing in the evolutionary series of vegetable crops from their ancestral forms to modern varieties and lines, including those needed for the analysis of domestication processes; introduction of crops and types of varieties novel for Russia; mobilization of the world’s best achievements in modern breeding, first of all in the newest breeding trends; mobilization of new genetic material -mutant lines, double haploid lines, and mapping populations.